Effects of concavity on tensile and fatigue properties in fibre laser welding of automotive steels. (January 2014) - Westerbaan, D.; Parkes, D.; Nayak, S. S.; Chen, D. L.; Biro, E.; Goodwin, F.; Zhou, Y.
<x content-type="archive" xml:space="preserve">Abstract</x> DP980 dual phase and high strength low alloy (HSLA) steels were welded, using fibre laser, with varying amounts of concavity to determine its effects on the tensile and fatigue properties. Higher concavity, 25 to 35%, was observed to reduce the tensile strength of the DP980 welds, while not affecting the tensile strength of HSLA welds. All welds exhibited lower fatigue resistance compared to their base metals. However, DP980 welds with higher concavity (25 to 35%) exhibited even lower fatigue resistance while HSLA welds showed similar performance regardless of changes in concavity. Concavity could be minimised by reducing welding power and increasing the welding speed.